Critical shifts in the global tourism industry: perspectives from Africa - Zhou, Zibanai (Springer Science and Business Media Deutschland GmbH, 2021)
The study investigates critical shifts impacting the international tourism space in contemporary times. Furthermore, the current study examines tourism policies and product development challenges faced by tourist regions as a consequence of market dynamics. Drawing upon a sample of thirty tourism experts in southern Africa, the critical shifts were identified and key among them include BRICS, terrorism, ageing population, and trophy hunting, are increasingly framing a new narrative for the future growth trajectory of the international tourism industry’s value chain in the context of Africa. A conclusion is reached that to attain long term sustainable development of the sunrise multi-trillion dollar industry, it is critical that tourism operators re-set and deploy sharpened strategies which are in synch with the realities obtaining in the broader operating environment. Policy recommendations and managerial implications are proffered.